1980
DOI: 10.1143/jjap.19.519
|View full text |Cite
|
Sign up to set email alerts
|

On the Determination of Trap Depth from Thermally Stimulated Currents

Abstract: A new method for estimating energy depths of traps from a thermally stimulated current with slow retrapping is described in detail. This method uses the maximum temperature Tp and the arbitrary temperature Ti at which the TSC intensity attains 1/m of the maximum value Im in the lower temperature region. The energy depth E is given by E=A((kTpTi)/(Tp-Ti)), where the coefficient A is a parameter which is determined to be about 0.5∼2.5 corresponding to the individual case of m=1.1∼5. The validity of this method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…In dielectric materials, the presence of deep traps may reduce the charge conduction at high fields (9). Here, thermally stimulated depolarization current (TSDC) is used to probe the trap states in the PEEU films with different nanofiller loadings (31,32), and the data recorded are presented in fig. S3.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In dielectric materials, the presence of deep traps may reduce the charge conduction at high fields (9). Here, thermally stimulated depolarization current (TSDC) is used to probe the trap states in the PEEU films with different nanofiller loadings (31,32), and the data recorded are presented in fig. S3.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Early dielectric spectroscope studies of PP revealed two dielectric relaxation processes, a dielectric relaxation at low temperature is associated with the glass transition (α relaxation) and the high temperature one (~ 100 °C) is associated with crystallization (β relaxation) [ 18 ]. TSDC is carried out to probe the depolarization peak and trap depth for the polymers associated with the high temperature polymer chain relaxation which is of interest of this study [ 19 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The method of TSDC used is different from that described by other researchers . On the one hand, the temperature of the material is increased, and at the same time, the polarized or nonpolarized current is measured.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The latent relaxation time is expressed by (3) : τ0=kTm2ETβexpETkTm where T m is the temperature corresponding to the maximum of TSDC. The integral part of (2) is almost zero at low temperatures, so (2) can be approximated by : I=AexpETitalickT …”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation